Pengaruh Model Pembelajaran Problem Based Intruction (PBI) Terhadap Kemampuan Pemecahan Masalah Matematis - Futri Hikma Fatona; Yusuf Hartono; Nora Surmilasari (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2019)
This study aims to determine the effect of the learning model of Problem Based Intruction (PBI) on mathematical problem solving abilities of class VIII students in Rantau Panjang Middle School 1. The research method that will be used in this research is the True Experimental Design method. the population in this study were all eighth grade students of SMP N 1 Rantau Panjang totaling 106 students. The samples taken in this study were 52 students consisting of 25 students in class VIII.1 as the experimental class and 27 students in class VIII.3 as the control class. Data collection techniques using tests. The research data were analyzed using the Mann-Whitney.The results of the analysis and discussion, it was concluded that there was a significant effect between the Problem Based Intruction (PBI) learning model on the mathematical problem solving abilities of class VIII students in Middle School 1Rantau Panjang.